PENGARUH STRUKTUR KEPEMILIKAN DAN TATA KELOLA PERUSAHAAN TERHADAP PERILAKU PENGAMBILAN RISIKO - Itan, Iskandar; Devina, Devina (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract” The goal of this research is to look into the impact of ownership concentration, managerial ownership, and corporate governance on corporate risk-taking using stock return volatility. This study's methodology is a quantitative approach that uses simple linear regression models and panel data. The sample for this study consists of manufacturing sector companies that were listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020. The purposive sampling method obtained 137 companies and 679 data for the sample. As a result, ownership concentration and corporate governance have negative and significant effects on corporate risk-taking, whereas managerial ownership has no significant effect. This study demonstrates that firms take significantly less risk when they have more concentrated ownership and good corporate governance. Keywords: Corporate Governance; Ownership; Risk-taking